2021
DOI: 10.22159/ajpcr.2022.v15i1.43553
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Profile of Children Admitted With Fever Without Focus for Less Than 7 Days Duration at Tertiary Care Center

Abstract: Objective: The objective of the study was to know about the etiology of acute undifferentiated febrile illness (AUFI) or fever without focus in children admitted at tertiary care hospital. Methods: A study was conducted at medical college, Jhalawar, for a period of 3 months. Pediatric patients presenting with fever for less than or equal to 7 days duration without focus, who required hospitalization were included in this study. Results: A total of 200 children enrolled in study. Male-to-female ratio was 1.9:1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…On clinical examination, out of 200 patents enrolled in our study, 151 (75.5%) patients had no specific clinical findings except fever, 41(20.5%) patients had Pallor, 27(13.5%) had Splenomegaly, 6(3%) patients had Icterus, 7(3.5%) patients had Rashes and 9(4.5%) had Hepatomegaly as clinical signs. In study done by Nagar R et al, 10 found that 28% cases had Pallor and 35% cases had Splenomegaly. In another study done by Desari R et al, 4 found 3.1% had Splenomegaly.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…On clinical examination, out of 200 patents enrolled in our study, 151 (75.5%) patients had no specific clinical findings except fever, 41(20.5%) patients had Pallor, 27(13.5%) had Splenomegaly, 6(3%) patients had Icterus, 7(3.5%) patients had Rashes and 9(4.5%) had Hepatomegaly as clinical signs. In study done by Nagar R et al, 10 found that 28% cases had Pallor and 35% cases had Splenomegaly. In another study done by Desari R et al, 4 found 3.1% had Splenomegaly.…”
Section: Discussionmentioning
confidence: 92%
“…On Gender basis it was found that, out of 200 patients enrolled, 117{58.5%} were Males and 83{41.5%} were Females (ratio M:F =1.4:1). In a study done by Nagar R et al 10 found that out of 200 cases, 132 (66%) were Males and 68 (34%) were Females (ratio M: F=1.9:1). One of the possible reasons for having male predominance in vector borne diseases could be more outdoor activity done by male subpopulation.…”
Section: Discussionmentioning
confidence: 96%